Strategi Media Sosial TikTok Nusantara TV dalam Meningkatkan Engagement - Agus Setiawan; Rori Hastomo (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
TikTok, as a rapidly growing platform, offers a variety of creative features that enable users to effectively reach a wider audience. This study discusses the TikTok social media strategy implemented by Nusantara TV to enhance engagement, as engagement significantly impacts a company’s public image. Using a qualitative approach, the research demonstrates how these strategies contribute significantly to increased engagement. The study analyzes Nusantara TV’s TikTok content strategy through the Stimulus-Organism-Response (SOR) framework. The strategy includes the use of up-to-date news content, short video formats, interactive Live Streams, and the use of hashtags. Audience responses are reflected through comments, likes, and shares, with a preference for educational content. As a result, there has been a significant increase in engagement and follower growth—from 5,000 to 80,000 in three months—along with improved audience loyalty toward Nusantara TV’s TikTok account. View counts rose organically from around 13 million in January, 40 million in February, and 86 million in March. The combination of content and tagging has helped boost both engagement and follower count on Nusantara TV’s TikTok.